(untitled) - Baillie, G. H. (London, 1979)
This is widely acknowledged as being one of the most important and informative books ever to appear on the subject of horology. The present work is a facsimile, produced by the original printers of the original publication. For accurate factual information, Baillies' work is as fresh today as it was when first written. It is a proper history covering nearly four centuries, with emphasis on original developments...
Keywords: Clocks and watches,Đo thời gian và đồng hồ